KUALITAS LAYANAN, ATMOSFER TOKO, DAN KEWAJARAN HARGA SEBAGAI PENENTU KEPUASAN DAN LOYALITAS DI KAISAR BARBERSHOP SEMARANG - Caesar, Jovanda; Hariyadi, Guruh Taufan; Nuryanto, Imam; Damar, Haunan (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2025)
This study analyzes the impact of service quality, store atmosphere, and price fairness on customer satisfaction and its effect on loyalty at Kaisar Barbershop Semarang. A quantitative approach using PLS-SEM was employed, with 145 purposively sampled respondents (criteria: customers who used the service at least twice in the last three months). Data was collected via a 7-point Likert scale questionnaire and analyzed using SmartPLS. Results show that service quality is the most dominant factor (path coefficient 0.732), followed by store atmosphere and price fairness (each 0.135). Customer satisfaction also significantly influences loyalty (0.935). These findings assist management in improving strategies to maintain customer loyalty in a competitive market